Implementasi Jaringan Tunnel Berbasis Eoip (Ethernet Over Ip ) Dengan Mikrotik Router Rb 2011 Il-Rm Di Silampari Tv Lubuklinggau - Armanto Armanto (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2017)
Designing an Eoip-Based Tunnel Network (Ethernet Over Ip) With Mikrotik Router Rb 2011 Il-Rm In Silampari Tv Lubuklinggau, compiled by armanto, Currently in Silampari Tv has two buildings in the suburbs That has two offices in different places with the distance Far enough, the first office in one studio is precisely located in Watervang and the two studios are in Sumber Agung Kota Lubuklinggau. In studio one is a production kitchen that processes video to run. Not connected to each other, so between studio one and setudio two can not do file sharing, VOIP, and the need for information exchange in other networks. Therefore I will create a computer network that can overcome the problems that have been complained by the Silampari TV by using MikroTik as its main tool and provide a solution that is quite economical and reliable for this problem, one of them with Tunnel. In this research used some tools like 6 unit pc which is used for client, swich as data communication media between utp cable, TP-Link Wireless Router fruit as hotspot and data distribution media from mikrotik one to mikrotik two, and two mikrotik rb 11 for Internet data and tunnel settings, Inteernet that supports this research is that can from one of the providers in the hole linggau namely B-NET